Effect of Ergonomic Gymnastics on Systolic Blood Pressure Among Individuals with Hypertension in Kaliasin Family Welfare Development - Diyan Mutyah; Hidayatus Sya’diyah; Sukma Ayu Candra Kirana; Ayu Citra Mayasari; Evi K (Universitas Nahdlatul Ulama Surabaya, 2022)
One of the things that can affect blood pressure is a lack of physical activity. Ergonomicgymnastics is an exercise that easy to learn and understand. This paper analyzes theeffect of ergonomic exercise on systolic blood pressure among individuals with hypertension in the Kaliasin family welfare empowerment. This research was a pre-experimental study with a One-group pre-posttest design. The sampling technique utilized non-probability sampling with the purposive sampling technique. In addition,the population was 20 individuals with hypertension in Kaliasin family welfareempowerment. Fifteen people met the inclusion criteria – 45-55 years old and had stageI hypertension with 140-159 mmHg systolic. The independent variable was ergonomicgymnastics, while the dependent variable was systolic blood pressure. Ergonomicgymnastics were performed six times for two weeks with 25-30 minutes in eachmeeting. In addition, the instruments were ergonomic gymnastics manuals with anobservation sheet and a sphygmomanometer. Data analysis utilized the Wilcoxonsigned-rank test with a significance level of 0.05. The results showed that mostrespondents had 155-159 mmHg in systolic blood pressure (40%) before the ergonomicgymnastic. Meanwhile, after the intervention, they had 145-149 mmHg (33.3%) and150-154 mmHg (33.3%). In addition, the Wilcoxon signed-rank test obtains ρ=0.001(α≤ 0.05). Thus, there was a difference in systolic blood pressure before and afterergonomic gymnastics. Ergonomic gymnastics can decrease systolic blood pressure.Individuals with stage I hypertension should perform ergonomic gymnastics routinely toavoid the complication of hypertension.